2011
DOI: 10.1038/ng.960
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies susceptibility loci for dengue shock syndrome at MICB and PLCE1

Abstract: Hypovolemic shock (Dengue shock syndrome (DSS)), is the commonest life-threatening complication of dengue. We conducted a genome-wide association study of 2,008 pediatric cases treated for DSS and 2,018 controls from Vietnam. Replication of the most significantly associated markers was carried out in an independent Vietnamese follow-up sample of 1,737 cases and 2,934 controls. Polymorphisms within two genes showed genome-wide significant association with DSS (Pmeta = 4.41 × 10−11, per-allele odds ratio (OR) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
148
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(155 citation statements)
references
References 32 publications
6
148
0
1
Order By: Relevance
“…Patients with focal segmental glomerulosclerosis have been found to have loss-of-function mutations in PLCe1, and PLCe1 itself interacts with transient receptor potential channel 6 (24)(25)(26)(27). Even more intriguing is the fact that a genome-wide association study identified the susceptibility loci for dengue shock syndrome at PLCe1 (28). Whether mutations in PLCe1 are directly responsible for this clinical syndrome remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with focal segmental glomerulosclerosis have been found to have loss-of-function mutations in PLCe1, and PLCe1 itself interacts with transient receptor potential channel 6 (24)(25)(26)(27). Even more intriguing is the fact that a genome-wide association study identified the susceptibility loci for dengue shock syndrome at PLCe1 (28). Whether mutations in PLCe1 are directly responsible for this clinical syndrome remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, given that host, 6 viral, and possibly vector-related factors [7][8][9] influence disease outcome, cross-sectional studies that compare primary and secondary infections may be confounded by many factors other than the serologic status of dengue at the point of infection. Cohort studies could address this question, although such studies are complex and resource intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on children with ADEM show that two-thirds recover completely over the course of several weeks. 8,11 In 2007, the International Pediatric Multiple Sclerosis Study Group proposed the presence of encephalopathy, multifocal affectation, and the absence of previous demyelinating events as diagnostic criteria for ADEM, all of which are present in this patient. 3,10 The diagnosis of ADEM in this patient was supported by remission of signs following treatment with intravenous methylprednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…1 This fact may support the hypothesis of genetic predisposition to develop ADEM; however, genome-wide association studies are required from a large populationbased research. 11 There is no standard treatment for ADEM. Steroids are used in high doses and diverse protocols use methylprednisolone or dexamethasone for 3-5 days, followed by oral steroids Figure 1.…”
Section: Discussionmentioning
confidence: 99%